2018
DOI: 10.1002/jsp2.1016
|View full text |Cite
|
Sign up to set email alerts
|

Facet joint degeneration in adolescent idiopathic scoliosis

Abstract: Adolescent idiopathic scoliosis (AIS) is a poorly understood deformity of the thoracolumbar spine which affects the intervertebral discs (IVDs) and the articular facet joints. The knowledge concerning facet joints in this context is very limited, although facet joint degeneration is a known contributor of back pain. In this study, a comprehensive investigation was performed to characterize the facet joint chondrocytes and extracellular matrix within the scoliotic spine. Surgically removed articular facet joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The increase in baseline gene expression of proteases MMP3 and MMP13 match extensive previous research showing a robust increase of these proteases in OA cartilage. Furthermore, it corroborates with immunohistochemistry findings in our previous study on scoliotic facet joint degeneration 4 . Gene expression analysis of TLRs revealed that chondrocytes from degenerating scoliotic cartilage had an elevated baseline expression of TLRs compared with the non‐degenerate non‐scoliotic cells.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The increase in baseline gene expression of proteases MMP3 and MMP13 match extensive previous research showing a robust increase of these proteases in OA cartilage. Furthermore, it corroborates with immunohistochemistry findings in our previous study on scoliotic facet joint degeneration 4 . Gene expression analysis of TLRs revealed that chondrocytes from degenerating scoliotic cartilage had an elevated baseline expression of TLRs compared with the non‐degenerate non‐scoliotic cells.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, we have recently reported facet joint osteoarthritis (OA) in AIS patients, although, how the altered biomechanics affect the facet joints is still unclear. Histologically, we found that scoliotic and non‐scoliotic facet joint OA share many characteristics such as fibrillation of the cartilage surface, erosion, fissuring, osteophyte formation, increased cell density and elevated expression of pro‐catabolic and pro‐inflammatory factors which suggests that they are closely related 4,9,10 …”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The fragmentation of chondroadherin is also characteristic of the disease, the cleavage site-specific for disc degeneration is represented in Table 2, making the chondroadherin fragment an efficient biomarker [127,137]. In addition, other SLRPs present enhanced fragmentation patterns in pathological human and canine intervertebral discs [138][139][140].…”
Section: Slrp Degradation and Cleavage In Skeletal Tissuesmentioning
confidence: 99%